2013
DOI: 10.1002/term.1830
|View full text |Cite
|
Sign up to set email alerts
|

Development of volume-stable adipose tissue constructs using polycaprolactone-based polyurethane scaffolds and fibrin hydrogels

Abstract: Adipose tissue engineering aims at the restoration of soft tissue defects and the correction of contour deformities. It is therefore crucial to provide functional adipose tissue implants with appropriate volume stability. Here, we investigate two different fibrin formulations, alone or in combination with biodegradable polyurethane (PU) scaffolds as additional support structures, with regard to their suitability to generate volume-stable adipose tissue constructs. Human adipose-derived stem cells (ASCs) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 29 publications
(49 reference statements)
2
33
0
Order By: Relevance
“…Adipose tissue development within these constructs was proven in a pilot study over 5 weeks in a nude mouse model. Utilizing an integrated arteriovenous bundle, distinct vascularization within the constructs in vivo was shown . However, the necessity and the impact of the implanted cells on tissue development in these constructs were not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adipose tissue development within these constructs was proven in a pilot study over 5 weeks in a nude mouse model. Utilizing an integrated arteriovenous bundle, distinct vascularization within the constructs in vivo was shown . However, the necessity and the impact of the implanted cells on tissue development in these constructs were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we used biodegradable polyurethane scaffolds in combination with a long‐term stable fibrin gel as cell carriers, which were seeded with ASCs, to develop volume‐stable, transplantable adipose tissue constructs. In a previous study, a comprehensive in vitro characterization displayed the viability and adipogenic properties of the cells in the cultured constructs . The aim of the present study was to evaluate the impact of the transplanted ASCs on tissue development in vivo by comparing ASC‐seeded versus unseeded constructs in a nude mouse model with a vascular pedicle in the constructs upon implantation.…”
Section: Introductionmentioning
confidence: 96%
“…[25] Fibrin is a versatile biopolymer that has a critical role in blood clotting, cellular-matrix interactions, wound healing, and angiogenesis, [29][30][31] and is widely used as a biomaterial for engineered adipose, dermal, and cardiovascular tissues. [32][33][34] Like most other natural materials though, the main disadvantages of using fibrin as a scaffold are low mechanical stiffness and rapid degradation, [35,36] both of which can be mitigated by incorporation of PEG, an FDA-approved polymer with a wide range of medical and industrial applications. [25,37,38] Based on this data, we hypothesized that subcutaneously injecting AFSC-seeded fibrin/PEG hydrogels in immunodeficient mice would both induce a fibrin-driven angiogenic response and promote AFSC-derived neovascularization.…”
mentioning
confidence: 99%
“…In experiments which followed the progress of implanted hydrogels for nearly a month, we observed that shrinkage of composites occurred at a same rate as matrices free of the metal component, dispelling concerns relating to a potential inhibition of the natural fibrinolysis process that could limit scaffold remodeling into tissue. For those tissue engineering applications where optimal shape integrity and stability of the scaffold are required for defined periods of time, HGNPs may be incorporated in hydrogel formulations designed to prolong the life of fibrin matrices, containing, for example, proteolytic or fibrinolytic inhibitors [23-26], cross-linking enzymes such as the transglutaminasa factor XIIIa [27] or reinforcing synthetic polymers such as polyethylene glycol [28] or polyurethane [29]. A remaining issue concerns the toxicity of HGNPs.…”
Section: Discussionmentioning
confidence: 99%